149k views
2 votes
Find g(6) when g(x) = x2-5

User Aflorezd
by
4.4k points

2 Answers

4 votes

Answer:

g(6) = 31

Step-by-step explanation:

If g(x) = x^2 - 5, that means to solve for g(6) you just have to replace the x in the equation with 6.

g(6) = 6^2 - 5

g(6) = 36 - 5

g(6) = 31

User AMiGo
by
5.1k points
6 votes
Answer:

g(6)=31

Step-by-step explanation:

We are given the function:
g(x)=x^2-5
We want to find g(6), therefore we should substitute 6 in for each x in the function.
g(6)=(6)^2-5
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, and Subtraction.
Evaluate the exponent. 6^2 is equal to 6*6 which is equal to 36.
g(6)=36-5
Subtract 5 from 36.
g(6)=31

g(6) is equal to 31 for the function g(x)=x^2-5
User Pkolodziej
by
4.8k points